Pelatihan Akuntansi berdasarkan SAK berbasis IFRS dengan menggunakan aplikasi MYOB disesuaikan dengan kebutuhan Industri serta E-Perpajakan (Pada SMK Bandung Barat 2 Jl. Raya Cihampelas No.88 KBB) - Romli, Romli; Anissa Yuniar Larasati; Purwanto; Vicky Dzaky Cahaya Putra; Rizki Indrawan; Wiwi Hartika (Fakultas Teknik Universitas Lancang Kuning, 2023)
The purpose of community service activities, especially for SMK students, is to improve human resource skills, by providing knowledge and skill development in using the MYOB application in preparing financial reports, as well as E-Taxation. Faced with the current developments in the industrial revolution 4.0 era, it has had a significant impact on the financial reporting process that was previously manual to become system-based, including in the field of taxation. The target community service is students of SMK West Bandung 2 Jl. Raya Cihampelas No. 88 KBB. It is hoped that after participating in this activity students will be able to understand the basic concepts of accounting, be able to compile financial reports with the MYOB application in accordance with the Statement of Financial Accounting Standards (PSAK), as well as fill out related to taxation electronically. Community service methods for SMK students by providing theoretical and practical knowledge as well as question and answer (discussion). From the process of increasing understanding of the Myob and E Tax applications, it will become a provision, especially for students who will pursue further education at a higher level or who will work to become more prepared and confident. Keywords: Basic Concepts of Accounting, Myob, Financial Statements, E-Taxation